Extrinsic and Intrinsic Aspects of The Adversarial System of Pakistan: Fact Finding Through Evidence - Bakhsh, Faiz; Ejaz, Naveed; Khattak, Fakharuddin; Jamshed , Jibran (Pakistan Journal of Humanities and Social Sciences, 2022)
Due to its foundations in the English and Magna Carta legal systems, Pakistan's legal system is fundamentally adversarial. The dominant idea that runs through Pakistani law is the adversarial paradigm. For the purpose of establishing facts, this method primarily relies on numerous types of evidence. However, the disadvantages of Pakistan's adversarial system to its sociopolitical and religious-economic environment outweigh its advantages. This paper explores Pakistan's adversarial judicial system in terms of its extrinsic and inherent characteristics, as well as its advantages and disadvantages for the country's legal system. This study discusses the adversarial legal system of Pakistan the extrinsic and intrinsic components of an adversarial system by in the light of constraints and benefits to the Pakistani legal system. The fact finding with the help of evidence and extrinsic and intrinsic aspects of the adversarial system of Pakistan are discussed in this study. There lacks an effective legal framework as well non enforcement of existing laws without proper checks and balances on the concerned departments and offices. There is a dire need to reform and update the existing legal framework in line with the modern world systems.